2020
DOI: 10.3329/jopsom.v38i2.47861
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress of Mothers Having Children with Thalassemia

Abstract: Background: Parents of children with thalassemia faces numerous challenges while coping various problems arises from the disease. Objective: The study was conductedto assess parenting stress of the mothers having children with thalassemia. Materials and Methods: This was a cross sectional study conducted amongmothers having children with thalassemia. A total of 253 mothers were included in this study conveniently.Data were collected by face to face interview by using a semi-structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Regarding to occupation of the studied caregivers, the results of the current study revealed that, more than four fifths of studied caregivers were housewives. These results corresponded with study performed by Mohiuddinet et al [19], whose conduct study in Bangladesh (study sample equal 253 mothers having children with thalassemia.) and entitled as "Parenting Stress of Mothers Having Children with Thalassemia" who found that, 82% of studied mothers were housewives.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding to occupation of the studied caregivers, the results of the current study revealed that, more than four fifths of studied caregivers were housewives. These results corresponded with study performed by Mohiuddinet et al [19], whose conduct study in Bangladesh (study sample equal 253 mothers having children with thalassemia.) and entitled as "Parenting Stress of Mothers Having Children with Thalassemia" who found that, 82% of studied mothers were housewives.…”
Section: Discussionsupporting
confidence: 90%
“…A study from Iran found that mothers of thalassemic children had signi cantly higher depression than mothers in the control group [12]. Regarding the mental health of the mothers with thalassemic children in Bangladesh, Mohiuddin et al (2020) studied only the parenting stress and found that the majority of the mothers faced moderate level of stress [13].…”
Section: Introductionmentioning
confidence: 99%